Prediction of pavement condition using markov chain method based on PCI and SDI assessment result - Hakim, Indri Nurtiyani; Fauziah, Miftahul; Chasanah, Faizul (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2025)
A pavement management system needs to be implemented as a form of road management to ensure that roads function properly. The Markov Chain model describes future pavement conditions to produce optimal highway maintenance. The research was carried out on Suprapto Street, Ahmad Yani Street, and Yos Sudarso Street in Indramayu Regency. Based on road conditions in 2024 by PCI and SDI assessment results, predictions are made by multiplying the initial condition vector by the transition probability matrix. Once the condition of the road is known, the proposed type of maintenance can be determined based on Ministerial Regulation of Public Work No. 13/PRT/M/2011, along with the costs required based on the maintenance cost history. The Markov Chain predictions show that road conditions will deteriorate and there will be an increase in severe damage over the years if no treatment is carried out. Maintenance action patterns vary; sections that experience a high level of damage will receive more serious treatment, and in the following year maintenance will decrease and then increase again according to the level of damage. The pattern of maintenance costs also follows the handling actions taken. Costs in the initial year were the highest, while most costs were spent on Suprapto Street.